MENILIK ULANG ARTI KELUARGA PADA MASYARAKAT INDONESIA - Amorisa Wiratri (Research Centre for Population, Indonesian Institute of Sciences, 2018)
Currently, social dynamic is growing fastly. A similar situation can also be seen in Indonesian societies, including in the smallest scale, which is family. This study aims to answer whether the definition of family that is used by the Indonesian government is still relevant to portrait the condition of societies in this country nowadays. This study used literature review as the primary data source and anthropological approach as an analysis tool. This article presents discussions on family dynamics in Indonesia, family and marriage, long distance family, as well as family and Indonesian culture. In conclusion, the family concept in Indonesia should not be constrained by structure, location and gender division. Therefore, Indonesia as a state should construct a more flexible definition of family to adjust community diversity and to shed lights on various family contexts and individual experiences.